Identification of Novel Mycobacterial Inhibitors Against Mycobacterial Protein Kinase G - Kanehiro, Yuichi; Tomioka, Haruaki; Pieters, Jean; Tatano, Yutaka; Kim, Hyoji; Iizasa, Hisashi; Yoshiyama, Hironori (Frontiers in Microbiology, 2018)
Protein kinase G (PknG) is a eukaryotic-like serine/threonine kinase that is expressed by Mycobacterium tuberculosis and promotes survival of mycobacteria in host macrophages by suppressing phagosome-lysosome fusion. Thus, compounds showing inhibitory activity against PknG are promising anti-mycobacterial agents. We therefore aimed to develop anti-mycobacterial agents by identifying new PknG inhibitors. A luciferase-based PknG kinase assay was used to screen potential inhibitors of PknG. We found that four compounds, namely AZD7762, R406, R406-free base, and CYC116, inhibited PknG activities. AZD7762, R406, and R406-free base promoted transfer of mycobacteria to lysosomes. These compounds also inhibited survival of M. bovis Bacillus Calmette-Guérin (BCG) inside human macrophages. Furthermore, R406 and R406-free base showed bactericidal activity against BCG in infected human macrophages without cytotoxicity. The PknG inhibitors identified in this study by the luciferase-based PknG kinase assay may be promising leads for the development of anti-mycobacterial agents.